European Security and the Third World (Czech Journal of International Relations, 1967)
The political development of the contemporary world provides an image of advice to look at contradictory and contradictory events and phenomena. I particularly highlight, on the one hand, the escalation of the barbaric and brutal intervention of American imperialism in Vietnam and, on the other hand, the relatively successful development of cooperation between the states of Eastern and Western Europe, until recently divided by the supposedly insurmountable barriers of the Cold War. This different development in different parts of the world is often understood and evaluated differently in the councils of the progressive movement, and different conclusions are drawn from it, especially when it concerns the means and methods of struggle that must be applied in the world revolution, democratic, anti-imperialist and peace movement.